Designing the SiMiTi Architecture: A Framework for Sustainable Digital Transformation in Intelligent Enterprises - Linggar Kiki Zakaria; Ibnu Akil; Azis Sukma Dhiana; Edhi Prayitno (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The rapid evolution of digital technologies has compelled organizations to rethink their transformation strategies to ensure long term sustainability. This study proposes the SiMiTi Architecture, a conceptual framework intended to guide sustainable digital transformation (SDT) within intelligent enterprises. Based on a systematic literature review of 35 peer reviewed articles published between 2021 and 2025, the framework integrates five essential constructs: Strategic Alignment (SA), Digital Capability (DC), Technology Adoption (TA), Organizational Agility (OA), and Environmental Dynamism (ED). The model emphasizes the importance of strategic coherence, digital readiness, and contextual responsiveness as foundational elements for effective SDT. Strategic alignment ensures consistency between digital initiatives and enterprise objectives; digital capability and technology adoption establish the technological foundation for innovation; organizational agility mediates adaptive implementation; while environmental dynamism moderates the model’s applicability across various industrial and regulatory settings. The SiMiTi Architecture is theoretically anchored in four major theories: the Resource Based View, Strategic Alignment Theory, Dynamic Capabilities Theory, and Contingency Theory. This research contributes to the academic discourse by addressing a critical gap in existing models, particularly the integration of sustainability principles into digital transformation frameworks. Practically, it offers a diagnostic and planning tool for organizations striving to implement future ready, responsible digital strategies. The study concludes by providing recommendations for aligning technological investments with sustainable development goals and outlines directions for future empirical validation across sectors.